Association of prothrombin complexe concentrate with venous thrombosis after cardiac surgery: a case-control study - Zheng, Qiaowei; Zhang, Liting; Liu, Tingting; Guan, Dong; Feng, Weiyi; Luo, Saisai (Frontiers in Cardiovascular Medicine, 2023)
Background: Prothrombin complex concentrate (PCC) enhances coagulation and controls bleeding. We aimed to assess whether perioperative infusion of PCC is associated with venous thrombosis after cardiac surgery.We conducted a case-control study of patients undergoing cardiac surgery at our hospital in 2021. Multivariate logistic regression was used to assess the correlation between perioperative PCC infusion and postoperative venous thrombosis in cardiac surgery. Stratified analysis was also performed by age, hospitalization days, and whether warfarin, warfarin combined with heparin, warfarin combined with antiplatelet drugs were used postoperatively.Results: Data from 161 patients undergoing cardiac surgery were included in the analysis. Of these, 37 (23.0%) patients in the case group developed venous thrombosis, and 124 (77.0%) patients in the control group did not develop venous thrombosis. In the analysis without adjustment for confounders (model 1), perioperative PCC infusion significantly increased the risk of postoperative venous thrombosis (OR: 3.10, 95% CI: 1.26-7.59, P=0.0135). In the model analysis adjusted for sex, age, and hospitalization days (model 2), perioperative PCC infusion was no longer significantly associated with the risk of postoperative venous thrombosis (OR: 1.76, 95% CI: 0.56-7.59, P=0.3317). In the fully adjusted model (model 3), there was a marginally significant association between perioperative infusion of PCC and the risk of postoperative venous thrombosis (OR: 0.03, 95% CI: 0.00-1.23, P=0.0637).Our findings show no significant association between perioperative PCC infusion in cardiac surgery and the development of postoperative venous thrombosis. Randomized controlled trials are needed to determine the causal relationship between perioperative PCC infusion and venous thrombosis in cardiac surgery.